Cores da mudança?: as revoluções coloridas e seus reflexos em política externa - Ortega, Felipe Afonso (2009)
Between 2003 e 2005, three countries from the former Soviet Union saw opposition movements coming to power, either directly, through presidential elections, or through the resignation of the incumbent leaders, following series of popular protests. This group of movements the rose revolution in Georgia, the Orange revolution in Ukraine and the Tulip Revolution in Kyrgyzstan was eventually called ´color revolutions`. The central goal of this dissertation is to analyze the foreign policies adopted after the color revolutions by each one of the three countries. The main concern is with the relations that emerged with Russia, a country that represented an important obstacle to the success of the three movements. Such an analysis can help to clarify to what extent the russian-american confrontation, so evident during the processes that led to the revolutions, kept present in the speeches and actions of the new governments